1989
DOI: 10.1172/jci114238
|View full text |Cite
|
Sign up to set email alerts
|

Role of catalytic and lysine-binding sites in plasmin-induced neutrophil adherence to endothelium.

Abstract: Plasmin resulted in increased neutrophil adherence to cultured ovine pulmonary artery endothelial cell monolayers in a concentration-dependent manner (102-40'7 M). The adherence response increased fivefold above baseline within 60 min after addition of plasmin (10-8 M) and the response persisted up to 30 min after removal of plasmin. The neutrophil adherence was mediated by the action of plasmin on neutrophils rather than endothelial cells. The response was the result of an increase in functional activity of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…The generation of plasmin on the surface of PMNs may lead to their activation. We have previously demonstrated that plasmin but not plasminogen causes PMN adherence to cultured endothelial cell monolayers, an effect mediated by the lysine binding sites on plasmin (Lo et al, 1989). In the present study, we examined the effects of either preformed plasmin or plasmin generated by plasminogen activators on the aggregation of PMN and the molecular basis for the response.…”
Section: I~cmentioning
confidence: 87%
See 1 more Smart Citation
“…The generation of plasmin on the surface of PMNs may lead to their activation. We have previously demonstrated that plasmin but not plasminogen causes PMN adherence to cultured endothelial cell monolayers, an effect mediated by the lysine binding sites on plasmin (Lo et al, 1989). In the present study, we examined the effects of either preformed plasmin or plasmin generated by plasminogen activators on the aggregation of PMN and the molecular basis for the response.…”
Section: I~cmentioning
confidence: 87%
“…The relationship between polymorphonuclear leukocytes (PMN) and the fibrinolytic system may be important in the pathogenesis of tissue injury during inflammation (Lo et al, 1989;Malik, 1990). For example, fibrin degradation products generated by plasmin during fibrinolysis after PMN function (Kazura et al, 1989).…”
Section: I~cmentioning
confidence: 99%
“…33 Plasmin induced neutrophil aggregation and increased neutrophil adhesion to endothelial cells in vitro, an effect that could be inhibited by tranexamic acid. 19,20,27 The plasmin-induced neutrophil adherence was mediated through an upregulation of CD18 neutrophil cell surface glycoprotein, reflecting neutrophil activation. These data suggest that plasmin is able to activate neutrophils, which can be abrogated by tranexamic acid.…”
Section: Discussionmentioning
confidence: 99%
“…26 In vitro, tranexamic acid potently inhibited plasmin-induced proinflammatory responses. 13,19,27 The fact that the formation of plasmin is one of the earliest-occurring events after intravenous administration of LPS, together with the recent findings that plasmin is able to induce several cellular proinflammatory responses, including activation of p38 MAPK, led us to hypothesize that plasmin may play a role in the induction of LPS-induced inflammatory pathways. To test this hypothesis, we studied the effect of tranexamic acid infusion on activation of coagulation, granulocytes, endothelial cells, and the cytokine network in healthy humans injected with a single dose of LPS.…”
mentioning
confidence: 99%
“…It is possible that the adhesion molecule CD18 is involved in the aggregation. CD18 is activated in neutrophils after stimulation with plasmin [100]. Expression of two types of adhesion molecules on endothelial cells and neutrophils may provide the basis of the CD18-P-selectin-mediated adhesion of neutrophils to endothelial cells.…”
Section: Plasmin-induced Cell Activationmentioning
confidence: 99%